Creation of the Argentina-Alzheimer's Disease Neuroimaging Initiative - Russo, María Julieta (2014)
The Alzheimer's Disease Neuroimaging Initiative (ADNI) is a multisite, longitudinal study that assesses clinical, imaging, genetic, and biospecimen biomarkers through the process of normal aging to mild cognitive impairment and dementia. We present the creation of the Argentina-ADNI - the first South American ADNI - and its effort to acquire data comparable with those gathered in other worldwide ADNI centers.